2006
DOI: 10.1016/j.joca.2005.08.011
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a passive muscle stretching protocol on the articular cartilage

Abstract: These findings suggest that the stretching protocol used was harmful to the previously immobilized articular cartilage. However, the same stretching protocol did not harm the cartilage of non-immobilized groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 24 publications
2
31
0
2
Order By: Relevance
“…The increase in the number of chondrocytes that was observed in the animals in the LG and LEG was also observed in studies by Renner, Carvalho, Soares, Mattiello-Rosa 11 and Del Carlo et al 23 . Other authors found a reduction in cellular density 24,36,37 .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The increase in the number of chondrocytes that was observed in the animals in the LG and LEG was also observed in studies by Renner, Carvalho, Soares, Mattiello-Rosa 11 and Del Carlo et al 23 . Other authors found a reduction in cellular density 24,36,37 .…”
Section: Discussionsupporting
confidence: 78%
“…Common symptoms of these nervous injuries include dormancy, paresthesia, weakness and atrophy of the effector muscles, as well as the impairment of the normal functions and movements of the lower limbs, since this musculature affects the motricity of the joints 3, 4 , including the ankle, which is responsible for providing a stable base of support for the body, in addition to effectively propelling it during locomotion 5 . Thus, nerve lesions lead to the disuse of the limb and, as a consequence, there is a reduction in the mechanical stimulus necessary to maintain the morphological properties of the joint [6][7][8][9] , which can lead to rigidity of the joint capsule and consequent restriction in movement 10 , as well as atrophic changes in the articular cartilage with a reduction in its thickness and the number of chondrocytes 11,12 . Moreover, according to Hui, McCarty, Masuda, Firestein, Sah 13 , the composition and function of synovial fluid are also altered in cases of joint injury or disease.…”
Section: Introductionmentioning
confidence: 99%
“…When loading of articular cartilage is reduced and it is deprived of mechanical stimuli, there is rapid deterioration of biochemical and biomechanical properties [21,23,30]. The lower limb joints are unloaded and restricted in movement in animals and in humans with spinal cord injuries [23].…”
Section: Discussionmentioning
confidence: 99%
“…The use of stretching to prevent and treat contractures after immobilization is supported by numerous animal studies [3,8,12,30,32,39,40]. Ample evidence from these animal studies suggests that contracture management can be achieved through repeated or sustained stretching in the case of contractures not attributable to injury to the central nervous system [3,8,10,39,40].…”
Section: Introductionmentioning
confidence: 99%
“…(16) , de forma semelhante à do presente estudo, avaliaram alterações na cartilagem articular de tornozelos de ratos, após protocolo de alongamento muscular passivo cíclico em animais previamente imobilizados por quatro semanas. O protocolo de alongamento utilizado foi repetição de 10 vezes de dorsiflexão manual por 60s com 30s de intervalo entre cada período, sete dias por semana, por três semanas.…”
Section: Discussionunclassified